Playing the field: video games and American studies - Pöhlmann, Sascha (De Gruyter Oldenbourg, 2019)
American Studies has only gradually turned its attention to video games in the twenty-first century, even though the medium has grown into a cultural industry that is arguably the most important force in American and global popular culture today. There is an urgent need for a substantial theoretical reflection on how the field and its object of study relate to each other. This anthology, the first of its kind, seeks to address this need by asking a dialectic question: first, how may American Studies apply its highly diverse theoretical and methodological tools to the analysis of video games, and second, how are these theories and methods in turn affected by the games? The eighteen essays offer exemplary approaches to video games from the perspective of American cultural and historical studies as they consider a broad variety of topics: the US-American games industry, Puritan rhetoric, cultural geography, mobility and race, urbanity and space, digital sports, ludic textuality, survival horror and the eighteenth-century novel, gamer culture and neoliberalism, terrorism and agency, algorithm culture, glitches, theme parks, historical guilt, visual art, sonic meaning-making, and nonverbal gameplay.
Keywords: Aufsatzsammlung; Intermedialität; Handlung; Erzähltechnik; Narrativität; Computerspiel; USA